Quality of raw milk n doublé purpose system in Cordoba (Colombia), in máximum and minmum precipitation conditions - Rodríguez-Rodríguez, Virginia Consuelo; Acosta-Ruiz, Arles Ferney; Calderón-Rangel, Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2015)
A concern in agricultural production is to obtain optimal food quality and harmless for human consumption. It has been proposed that excellent quality milk must have high percentages of protein, fat, total solids and low counts of mesophilic, somatic cell-count (SCC) plus free of inhibitors to ensure their safety. The objective was to determine the physicochemical quality and udder health in raw milk, from dual purpose livestock companies in Cordoba Colombia, and at the same time, to compare these data with periods of high and minimal rainfall to see the physicochemical differences and udder health in each period. Using a non—probabi|ity sampling and descriptive study periods of maximum and minimum rainfall, raw milk samples were collected from 127 cattle enterprises. lt was determined: the percentage of acidity, fat, non-fat solids, total solids and somatic cell count. The data obtained were analyzed using descriptive statistics INFOSTAT. These values were within the normal range, with variations related to the time it was sampled.